Butterfly arm stroke symmetry: two-dimensional analysis simply using the mobile phone - Maia, F.; Almeida, A.; Lazari, J.; Roriz, P.; Marcelino, R.; Figueiras, T. (Motricidade, 2019)
The aim of this study was to analyse the butterfly swimming technique, namely the arm stroke symmetry, using an ecological methodology. Nowadays, it is possible to reduce the lab - field gap, by using simple, affordable and reliable smart phones and free apps for motion analysis. Swimming coaches can easily use technology to empower their swimmers and to make them understand the importance of a good swimming technique. As a simultaneous technique, symmetry is very important to prevent lateral misalignment of the body (Maglisho, 2003; Saders et al., 2011). In this case, we use an iPhone 6+ and the Kinovea® program to analyse the symmetry of two different moments of a butterfly non-breathing arm stroke, both out and under the water.